Functional type 1 regulatory T cells develop regardless of FOXP3 mutations in patients with IPEX syndrome. - Passerini, Laura; Di Nunzio, Sara; Gregori, Silvia; Gambineri, Eleonora; Cecconi, Massimiliano; Seidel, Markus G; Cazzola, Giantonio; Perroni, Lucia; Tommasini, Alberto; Vignola, Silvia; Guidi, Luisa; Roncarolo, Maria G; et al. (Eur J Immunol, 2011)
Mutations of forkhead box p3 (FOXP3), the master gene for naturally occurring regulatory T cells (nTregs), are responsible for the impaired function of nTregs, resulting in an autoimmune disease known as the immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome. The relevance of other peripheral tolerance mechanisms, such as the presence and function of type 1 regulatory T (Tr1) cells, the major adaptive IL-10-producing Treg subset, in patients with IPEX syndrome remains to be clarified. FOXP3(mutated) Tr1-polarized cells, differentiated in vitro from CD4(+) T cells of four IPEX patients, were enriched in IL-10(+) IL-4(-) IFN-γ(+) T cells, a cytokine production profile specific for Tr1 cells, and expressed low levels of FOXP3 and high levels of Granzyme-B. IPEX Tr1 cells were hypoproliferative and suppressive, thus indicating that FOXP3 mutations did not impair their function. Furthermore, we isolated Tr1 cell clones from the peripheral blood of one FOXP3(null) patient, demonstrating that Tr1 cells are present in vivo and they can be expanded in vitro in the absence of WT FOXP3. Overall, our results (i) show that functional Tr1 cells differentiate independently of FOXP3, (ii) confirm that human Tr1 and nTregs are distinct T-cell lineages, and (iii) suggest that under favorable conditions Tr1 cells could exert regulatory functions in IPEX patients.
Keywords: Cell Differentiation; Cell Lineage; Cells, Cultured; Enteritis; Forkhead Transcription Factors; Genetic Diseases, X-Linked; Humans; Immunity, Innate; Interleukin-2 Receptor alpha Subunit; Mutation; Polyendocrinopathies, Autoimmune; Syndrome; T-Lymphocytes, Regulatory